Agroclimatic indices across the Canadian Prairies under a changing climate and their implications for agriculture. (19th September 2021) - Chipanshi, Aston; Berry, Mark; Zhang, Yinsuo; Qian, Budong; Steier, Garrett
Abstract: With the objective of trying to understand the adaptability of agriculture across the Canadian Prairies under climate change, simple‐to‐use agroclimatic indices were calculated for the base climate period of 1981 to 2010 and for both the medium (RCP4.5) and high (RCP8.5) emission projections extending to the distant future (2071–2100). The agroclimatic indices included the Effective Growing Degree Days (EGDDs), Growing Season Length (GSL), the Climate Moisture Index (CMI), and the Temperature Humidity Index (THI). For climate change in 30‐year periods, these indices were calculated as multi‐model ensembles of six Global Climate Models recommended under the Coupled Model Intercomparison Project Phase 5 (CMIP5) for the study area. We found that the GSL, EGDDs, CMI, and THI were amplified above the values of the base climate period in the order of 40–50 days, 600–1200 heat units, −100 to −120 mm and 3–4 THI units by the close of the distant future (2071–2100) under the RCP4.5 and RCP8.5, respectively. This amplification has implications on where crop and livestock production could become more suitable or riskier in future. Opportunities include expanding crop and livestock production to more northerly regions which currently have insufficient heat units, a short growing season and unfavourable temperature humidity thresholds for livestock production. Moisture deficits will continue to be the greatest risk during the growing season under climate change scenarios but options exist to implement adaptive measures such as staggering seeding times to take advantage of moisture availability in the spring and autumn seasons and crop substitution. This study has relevance for policy and program formulation and implementation in Canada's agricultural regions and potentially, other areas of the world with similar climate change outcomes. Abstract : The Effective Growing Degree Days, Growing Season Length, Climate Moisture Index and the Temperature Humidity Index were amplified over their climatological values for medium (RCP4.5) and high (RCP8.5) emission scenarios and found favourable for cool season crops and ranching operations with the potential to expand these activities to the northern edges of the agricultural zone. Due to favourable conditions in the southern areas of the Prairie Provinces, growing of warm season crops will likely become more prevalent than it is today. Water deficits will require careful management nevertheless.